Global Research Trends in Endometrial Hyperplasia (2002–2021): A Bibliometric Analysis and Visualization Study - Mina, Angeliki (Ibnosina Journal of Medicine and Biomedical Sciences, 2023)
Introduction This article quantifies the research contribution related to endometrial hyperplasia (EH).Materials and Methods We searched the Scopus database in 2002 to 2021.Results A total of 6,422 were retrieved; 1,906 were open access; 5,602 in English. The number of published papers showed rising productivity over the last 20 years ranging from 261 to 425. There were 5,034 research articles and 1,388 reviews. The most prolific authors were Zullo, F (30), Mirkin, S (28), Archer, DF (27), and Insabato, L (26). The top involved journals were the Gynecologic Oncology Journal (144), European Journal of Gynaecological Oncology (114), and International Journal of Gynecological Pathology (105). The United States was the most dominant country, with 1,592 articles, followed by China (601) and Italy (435). The most actively involved institutions were the University of Texas MD Anderson Cancer Center (77), followed by Fudan University (63) and Harvard Medical School (62). The top funding sponsors were the National Cancer Institute (178), the National Institutes of Health (177), and the National Natural Science Foundation of China (107). The top three most cited articles received 1,182, 746, and 600 citations, respectively.Conclusion This study defines the prolific researchers, institutions, journals, and countries as a good starting to bridge gaps in research activity.
Keywords: bibliometric analysis; citation analysis; menopause; endometrial hyperplasia; endometrial cancer; research; visualization analysis